Abundance, composition and natural infection of Anopheles mosquitoes from two malaria-endemic regions of Colombia (2017)
ABSTRACT: Introduction: In Colombia there are three Anopheles species implicated in malaria transmission as primary vectors; however, the local role of some Anopheles species must still be defined. Objective: To determine the abundance, composition and natural infection rates for Anopheles mosquitoes with Plasmodium spp. in two malaria-endemic regions of Colombia. Materials and methods: Anopheles mosquitoes were collected using the human-landing catches and while resting in livestock corrals in nine localities of two malaria-endemic regions of Colombia. Mosquitoes were morphologically identified and confirmed by PCR-RFLP-ITS2. Identified mosquitoes were processed and tested for Plasmodium parasite infection by ELISA and ssrRNA-based nested PCR. Results: We collected 1,963 Anopheles mosquitoes corresponding to nine species. The most abundant species were Anopheles nuneztovari (53.5%) and A. darlingi (34.5%), followed by A. triannulatus s.l. (6%), and other species (≈5.9%). Three species were naturally infected with Plasmodium spp.: A. darlingi, A. nuneztovari and A. triannulatus s.l. Conclusions: Natural infection of A. darlingi and A. nuneztovari indicate that these malaria vectors continue to be effective carriers of Plasmodium in the localities under study in Valle del Cauca and Chocó. Additionally, the infected A. triannulatus s.l. collected in livestock corrals in the locality of the department of Córdoba suggests the need for further studies to define the epidemiological importance of this species given its abundance and opportunistic anthropophilic behavior.